Experimental and Simulation-Based Study on Thermal Runaway Characteristics of 18650 Lithium-Ion Batteries and Thermal Propagation Patterns in Battery Packs - Yao Yao; Xu Peng; Lei Gao; Haozhe Xing; Xiaohui Xu; Juan Gu; Lu Liu; Songlin Yue; Yanyu Qiu; Youning Wang; Zhi Zhang (Batteries)
The thermal runaway of lithium-ion batteries is a critical factor influencing their safety. Investigating the thermal runaway characteristics is essential for battery safety design. In this study, the thermal runaway characteristics of 18650 lithium-ion batteries under different SOCs were systematically analyzed by experiment and simulation. It was found that at high SOC (100%), the highly lithium state accelerated lattice oxygen release, promoted the formation of LiNiO and intensified electrolytic liquid oxygenation combustion, while at low SOC (20%), the reduction environment dominated, and the metal Ni and residual graphite were significantly enriched. Gas analysis shows that CO2 and H2 account for more than 80%, and their proportion is regulated by SOC. Temperature and pressure monitoring showed that the increase in SOC significantly increased the thermal runaway peak temperature (100% SOC up to 508.4 °C) and pressure (0.531 MPa).The simulation results show that when the battery pack is out of control, the ejection fire and explosion pressure wave are concentrated in the middle and upper region (overpressure up to 0.8 MPa). This study reveals the mechanism by which SOC affects the path of product and gas generation by regulating the oxidation/reduction balance, which lays a theoretical and simulation foundation for the safe design of batteries and the quantitative evaluation of thermal runaway.